Thermal and light-induced spin transition in a nanometric film of a new high-vacuum processable spin crossover complex. Issue 33 (13th August 2018) - Atzori, Matteo; Poggini, Lorenzo; Squillantini, Lorenzo; Cortigiani, Brunetto; Gonidec, Mathieu; Bencok, Peter; Sessoli, Roberta; Mannini, Matteo
Abstract : Herein, we report the identification of a novel high-vacuum processable spin-crossover complex which can be efficiently used to prepare continuous ultrathin films with retention of switchable magnetic properties. Abstract : Spin crossover complexes are among the most studied classes of molecular switches and have attracted considerable attention for their potential technological use as active units in new multifunctional devices. A fundamental step towards a practical implementation is their effective processability into thin films. Crucially, the physical property of technological interest shown by these materials in the bulk phase has to be retained once they are deposited on a solid surface. These conditions are not easily satisfied by most of the intrinsically fragile coordination compounds, either because the material processing methods can compromise their molecular structure, or the interaction between the molecule and the surface can induce drastic changes in the resulting properties. Herein, we report the identification of a novel high-vacuum processable spin-crossover complex, [Fe(qnal)2 ] (qnal = quinoline-naphthaldehyde), and the preparation of a 50 nm sublimated film of this molecular switch on gold. X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS) were used to investigate the composition and the temperature- and light-induced spin-crossover of the deposited material, providing full evidence of the capability of this molecular system to be efficiently processed into nanometric films with retention of its switchable magnetic properties.